A study of an effective UPTMCAA website design - Cavizo, Ma. Josefina B.
The TMCAA is an organization that needs collaboration from its community. To communicate with the alumni is very difficult after graduation, the alumni association remains inactive. There is a need for the TMCAA to differ their approach in connecting with the TMC community especially the alumni. Effective communication and collaboration are the keys to revamp the organization. Making use of the internet as a tool for collaboration is the best option for collaboration among organizations especially for an alumni association.